2022
DOI: 10.1111/1365-2435.14098
|View full text |Cite
|
Sign up to set email alerts
|

Every hooked beak is maintained by a prey: Ecological signal in cephalopod beak shape

Abstract: 1. Beaks are among the few hard parts of coleoid cephalopods and are informative for species identification. Although mandible shape has been shown to be adaptive in many vertebrate taxa, it has been suggested that the shape of coleoid beaks does not bear any ecological signal. Yet, previous studies only explored beak shape in 2D and none have provided an in-depth investigation of the potential relationship with ecological variables such as habitat use or diet.2. The goal of the present study was to understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 84 publications
1
23
0
Order By: Relevance
“…Specifically, Fernández-Álvarez et al (2020) studied impacts of developmental malformations of the buccal mass on the trophic position of Eledone cirrhosa and found that the habitat and the trophic position were not significantly affected by the malformations. Other authors found significant differences in the beak shapes of pelagic and benthic species in relation to their trophic levels (Roscian et al, 2022), between species living in coastal and oceanic habitats (Pacheco-Ovando et al, 2021) and between species/populations living in different feeding habitats (Pacheco-Ovando et al, 2021). New phylogenomic techniques applied to cephalopods (Anderson and Lindgren, 2021;Sanchez et al, 2021;Fernández-Álvarez et al, 2022) may help to assess which morphological characters of the beaks are determined by phylogeny and which are explained by other drivers.…”
Section: Taxonomy and Beak Morphologymentioning
confidence: 99%
See 4 more Smart Citations
“…Specifically, Fernández-Álvarez et al (2020) studied impacts of developmental malformations of the buccal mass on the trophic position of Eledone cirrhosa and found that the habitat and the trophic position were not significantly affected by the malformations. Other authors found significant differences in the beak shapes of pelagic and benthic species in relation to their trophic levels (Roscian et al, 2022), between species living in coastal and oceanic habitats (Pacheco-Ovando et al, 2021) and between species/populations living in different feeding habitats (Pacheco-Ovando et al, 2021). New phylogenomic techniques applied to cephalopods (Anderson and Lindgren, 2021;Sanchez et al, 2021;Fernández-Álvarez et al, 2022) may help to assess which morphological characters of the beaks are determined by phylogeny and which are explained by other drivers.…”
Section: Taxonomy and Beak Morphologymentioning
confidence: 99%
“…Several studies revealed the potential of beak shape analysis in ecological studies (Fernández-Álvarez et al, 2020;Pacheco-Ovando et al, 2021;Roscian et al, 2022). Specifically, Fernández-Álvarez et al (2020) studied impacts of developmental malformations of the buccal mass on the trophic position of Eledone cirrhosa and found that the habitat and the trophic position were not significantly affected by the malformations.…”
Section: Taxonomy and Beak Morphologymentioning
confidence: 99%
See 3 more Smart Citations